Full-length amyloid-beta (1-42(43)) and amino-terminally modified and truncated amyloid-beta 42(43) deposit in diffuse plaques. - Iwatsubo, T. (1996)
The amino- and carboxyl-terminal properties of the amyloid-beta (A beta) peptides deposited in diffuse plaques, one of the earliest forms of A beta deposition, were examined in the brains of patients with Down's syndrome and Alzheimer's disease and in aged individuals without dementia by immunocytochemistry. This was done using a panel of antibodies that specifically discriminate the terminal structures and modifications at the amino and carboxyl termini of A beta. Diffuse plaques found in the cerebral and cerebellar cortex, neostriatum, and hypothalamus of Down's syndrome, Alzheimer's disease, and nondemented brains were strongly immunoreactive for A beta N1(L-Asp), A beta N1(L-isoAsp), A beta N1(D-Asp), and A beta N3(pyroGlu) and weakly positive for A beta N11(pyroGlu) and A beta N17(Leu). Diffuse plaques also were positive for A beta 42(43) but negative for A beta 40, using carboxyl-terminal-specific anti-A beta antibodies. These results suggest that the amino termini of the A beta species that initially deposit in diffuse plaques begin with A beta N1(Asp) with or without structural modifications (isomerization and racemization), as well as with A beta N3(pyroGlu), and terminate preferentially at A beta 42(43) rather than A beta 40.